2015
DOI: 10.1038/ijo.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, cardiorespiratory fitness and cardiometabolic risk factors in youth from Portugal and Mozambique

Abstract: Portuguese and Mozambican youth differ in their cardiometabolic risk profiles, body weight and cardiorespiratory fitness, favoring Portuguese. Overweight/obesity and low cardiorespiratory fitness levels are related to a worse cardiometabolic risk profile, being relevant to design public health intervention strategies to reduce excess weight and increase cardiorespiratory fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(44 reference statements)
1
9
0
2
Order By: Relevance
“…It is not surprising that more obese individuals have a higher prevalence of metabolic syndrome; one of the fi ve metabolic syndrome components directly refl ects the degree of adiposity. In our study, we also confi rmed that more obese individuals are more likely to have metabolic syndrome (dos Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…It is not surprising that more obese individuals have a higher prevalence of metabolic syndrome; one of the fi ve metabolic syndrome components directly refl ects the degree of adiposity. In our study, we also confi rmed that more obese individuals are more likely to have metabolic syndrome (dos Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…Novel data standardisation techniques also allow for meaningful international comparisons of 20mSRT performance in youth 24. Recent studies have identified large variability in children's 20mSRT performance within and between countries,6 15 25–27 which may be associated with broad population-level socioeconomic, cultural and policy factors (henceforth referred to as socioeconomic indicators). Consequently, as a surveillance instrument, the 20mSRT could help identify populations with high CRE and provide insights into broad socioeconomic indicators that may inform intervention, programme and/or policy targets to help improve CRE in other populations, especially those with low CRE.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Dos Santos and colleagues in Maputo reported the prevalence of overweight/obesity to be 5.0%/6.0% in boys and 11.2%/9.1% in girls [ 98 ]. Dos Santos et al study also in Maputo among 323 adolescents aged 10 to 15 years reported the prevalence of overweight/obesity to be 7.5% in boys and 21.0% in girls [ 99 ]. In the Khartoum State of Sudan, Nagwa et al observed that, the prevalence of overweight and obesity were 10.8 and 9.7% in adolescents 10 to 18 years old [ 100 ]; while Salman et al found 14.8% overweight and 10.5% obesity among children between 6 and 12 years [ 101 ].…”
Section: Resultsmentioning
confidence: 99%